Unilateral subarachnoid block for Anesthesia and analgesia in Elderly undergoing femoral thrombectomy - EL Araby Abd ELhameed, Sally Mohamed; Sadek EL Attar, Hala Abdel; Mohammed Ali Mohammed, Amani Abdel Azeem Aly; Nermeen (Journal of Neonatal Surgery, 2024)
Unilateral subarachnoid block (USAB) is a refined form of spinal anesthesia designed to limit the sensory and motor blockade to one side of the body. This selective distribution provides adequate surgical anesthesia while minimizing hemodynamic instability and reducing the spread of the block to the non-operative side. USAB has gained increasing interest in lower-limb surgeries, high-risk patients, and elderly populations because it offers better cardiovascular stability, lower incidence of hypotension, and faster postoperative recovery when compared with conventional bilateral spinal anesthesia. Several technical factors—such as patient positioning, injection speed, baricity of local anesthetic, and needle orientation—play critical roles in achieving a successful unilateral block..